Rethinking the colonial state - Rud, Søren; Ivarsson, Søren (Emerald Publishing, 2017)
This volume addresses the analytical challenges of the colonial state from a variety of theoretical and thematic angles, and across a range of empirical cases that stretch over a vast span historically and geographically, to provide a new approach to analyzing the colonial state and its governmental practices.
Keywords: Colonies -- Administration.; Colonization.; elektronické knihy; electronic books